Comparison of infrapatellar and subcutaneous adipose tissue stromal vascular fraction and stromal/stem cells in osteoarthritic subjects. (16th July 2012) - Pires de Carvalho, Pedro; Hamel, Katie M.; Duarte, Robert; King, Andrew G. S.; Haque, Masudul; Dietrich, Marilyn A.; Wu, Xiying; Shah, Forum; Burk, David; Reis, Rui L.; Rood, Jennifer; Zhang, Ping; et al.
Abstract Since inflammatory mechanisms have been postulated to link obesity to osteoarthritis, the current study evaluated the ratio of immune cells to multipotent stromal cells within the infrapatellar fat pad (IPFP) and subcutaneous adipose tissue (SQ) of the knee; each depot has potential as a source of regenerative cells. The immunophenotypes of stromal vascular fraction (SVF) and adipose‐derived stem cells (ASCs) of the IPFP and SQ were determined in tissues from osteoarthritic subjects (n = 7) undergoing total knee replacement. Based on a subset of surface antigens, the immunophenotype of ASCs from SQ of OA subjects was not significantly different from that of relatively healthy and leaner subjects undergoing elective liposuction surgery. Flow‐cytometry comparison of SVF cell populations in the IPFP of OA subjects resembled those within the subject's own matched SQ, with the exception of the endothelial marker CD31+, which was significantly greater in cells from SQ. In the OA subjects, lower numbers of capillary‐like structures and higher numbers of stromal and alkaline phosphatase colony‐forming units in the IPFP vs SQ were consistent with this finding; however, ASCs from both depots in OA subjects exhibited comparable adipogenic and osteogenic differentiation potential. Thus, the IPFP contains an ASC and immune cell population similar to that of donor‐matched SQ, making it an alternative ASC source for tissue regeneration. Further studies will be needed to determine whether IPFP immune cell infiltrates play an aetiological role in osteoarthritis equivalent to that shown in diabetes associated with obesity. Copyright © 2012 John Wiley & Sons, Ltd.